Enhancing Fourth-Grade Students’ Dance Skills through Kabela Traditional Dance Using Audiovisual Media - Kono, Putri Cintia; Pulukadang, Wiwy Triyanty; Pulukadang, Mimy Astuty; Aya Ragab (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective:  This research aimed to improve fourth-grade students' ability to perform the traditional Kabela dance at SD Laboratorium Universitas Negeri Gorontalo using audio-visual media. Theoretical framework: The study is based on multimodal learning, particularly multimedia learning theory, which suggests that combining visual and auditory elements enhances understanding and coordination, especially in kinesthetic activities like dance. Literature review:  Previous studies highlight the effectiveness of audio-visual media in teaching dance by providing clear visual models, improving movement replication, and fostering engagement. It also emphasizes the importance of cultural competence in dance education. Methods: A classroom action research design was employed with two cycles, each consisting of two meetings. Data were collected through observations, performance tests, and documentation, assessing students' skills in movement, rhythm, and expression. Results: The results revealed a significant improvement in students’ performance in the Kabela dance after the implementation of audio-visual media. In the first cycle, only 8 students (44%) achieved satisfactory performance. However, in the second cycle, 16 students (89%) demonstrated mastery of the dance movements. The use of audio-visual media was shown to be an effective tool in enhancing students' understanding, coordination, and expression in performing the Kabela dance. Implications: The study suggests that audio-visual media is an effective tool for teaching traditional dance and improving students' cultural and artistic competence, especially in Seni Budaya dan Prakarya (SBDP) subjects. Novelty: This research introduces the use of audio-visual media to teach the Kabela dance, showing its potential to enhance dance learning outcomes and cultural appreciation in primary education.